Treatment of adult ALL patients with third-generation CD19-directed CAR T cells: results of a pivotal trial - Schubert, Maria-Luisa; Schmitt, Anita; Hückelhoven-Krauss, Angela; Neuber, Brigitte; Kunz, Alexander; Waldhoff, Philip; Vonficht, Dominik; Yousefian, Schayan; Jopp-Saile, Lea; Wang, Lei; Korell, Felix; Keib, Anna; et al. (Journal of hematology & oncology, 2023)
Third-generation chimeric antigen receptor (CAR)-engineered T cells (CARTs) might improve clinical outcome of patients with B cell malignancies. This is the first report on a third-generation CART dose-escalating, phase-1/2 investigator-initiated trial treating adult patients with refractory and/or relapsed (r/r) acute lymphoblastic leukemia (ALL).
Gesehen am 02.02.2024